Microsurgery and external fixation in orthoplastic reconstruction of tibial injuries - Toia, Francesca; Zabbia, Giovanni; Scirpo, Roberto; Pirrello, Roberto; Nalbone, Lorenzo; Cordova, Adriana (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2019)
Background “Orthoplastics” is a relatively new approach to lower limb reconstruction, where an integration of both plastic and orthopedic expertise is required, together with the availability of well-equipped facilities. Acute shortening and long-term frames for lengthening are generally considered alternatives to length preservation and soft tissue microsurgical reconstruction, but an integration of external fixation and reconstructive microsurgery is gaining an increasing role with refinements of joint approaches.Material and methods Data on sixteen patients who underwent microsurgical lower limb reconstruction and external fixation with an orthoplastic approach, following acute or chronic tibial injury, were retrospectively reviewed. All patients presented a post traumatic soft tissue defect associated with a Gustilo III tibial fracture or a tibial septic pseudarthrosis. Data on type and timing of bone and soft tissue reconstruction, outcomes, complications and need for re-operation were extrapolated and compared to an historic group of patients treated with an orthopedic-based approach.Results In the orthoplastic group, soft tissues were reconstructed with an ALT flap in most cases; a muscle-sparing VL or ALT-VL chimeric flap was necessary in cases with a very extensive defect. In the orthopedic group, soft tissues were left to heal by second intention or patients were lately referred to plastic surgeons. Statistical comparison between the two groups has showed significant differences on the following data: time for soft tissue healing, time to bone union, number of reinterventions, post-operative deep infection rate, time to return to work.Conclusion The orthoplastic approach to complex leg defects yields shorter treatment time and better functional results compared to the orthopedic-based approach. External fixation and microsurgical reconstruction are not necessarily alternative procedures but can integrate in an orthoplastic path to address at best both soft tissue and bone reconstruction.
Keywords: Microsurgery; orthoplastic reconstruction; lower limb reconstruction; external fixation